The Application of Competency-based Approach in the Study of Human Capacity - TOLSTOVA, Irina Edvinovna; KALOSHINA, Tatiana Yurievna; LEBEDEVA, Julia Veniaminovna; KOVALYEVA, Olesya Sergeyevna (Journal of Advanced Research in Law and Economics, 2017)
When writing this article, the main objective was to study the human capacity from the perspective of competency-based approach. An analysis of scientific literature allowed the authors to consider various approaches to the definition of terms ‘competence’, ‘competency’, and ‘competency-based approach’. In the article the authors point out that stands out two levels of competence. First level – competences needed each and everyone skilled in the modern society (let us call them ‘basic’), second – competences needed the representative of specific profession (let us call them ‘special’). However, as we can see based on the results available to us, almost all conducted studies and developments had a theoretical nature, the product of which are the above theories. If we set for ourselves the practical, applied task, which will result in the application of competency-based approach in a particular organization (and further in a single industry, field) we immediately are faced with a necessity to develop a third level – competencies for a specific position, a specific workplace. This problem can be solved by the variation mechanism of basic and special competencies based on the significance for each individual position.